Law Enforcement of The Criminal Offence of Cap Djie Kie Gambling in Sragen Regency - Taufik Hidayat; Muchamad Iksan (Universitas Muhammadiyah Surakarta, 2025)
Law enforcement against cap djie kie gambling in Sragen Regency aims to minimize the negative impacts of this illegal activity. This study aims to discuss: 1). Law enforcement against cap djie kie gambling crimes in Sragen Regency, 2). Factors that hinder law enforcement against cap djie kie gambling crimes in Sragen Regency, 3). Sslam's perspective on cap djie kie gambling. This research method uses an empirical juridical legal approach that analyzes regulations and their implementation in the field. This type of research uses descriptive research. The data in this study use primary data and secondary data. The results of the study discuss: 1) revealing that law enforcement is based on Article 303 paragraphs 1 and 2 of the Criminal Code which provide criminal sanctions for perpetrators and intermediaries of gambling. This regulation is intended to combat illegal gambling practices and maintain public order. This is reflected in Decision Number 155 / Pid.B / 2024 / PN Sgn which states that the defendant is guilty of committing a criminal act of gambling. That the perpetrators of gambling are prosecuted by law enforcement from the police to the courts that examine and decide guilty and legally prove the defendants to have gambled in Sragen Regency. 2). Obstacles to law enforcement are influenced by human resource factors, lack of legal understanding by the community, local cultural influences, limited infrastructure, and a very large area. 3). From an Islamic perspective, gambling practices have been clearly regulated in the Qur'an. Surah Al-Maidah Verses 90-91 and Surah Al-Baqarah Verse 219 emphasize that gambling has a destructive impact and is classified as a major sin that must be avoided.